Monocytes differentiated into macrophages and dendritic cells in the presence of human IFN-λ3 or IFN-λ4 show distinct phenotypes. Issue 2 (17th November 2020) - De, Manjarika; Bhushan, Anand; Chinnaswamy, Sreedhar
Abstract: Human IFN-λ4 is expressed by only a subset of individuals who possess the ΔG variant allele at the dinucleotide polymorphism rs368234815. Recent genetic studies have shown an association between rs368234815 and different infectious and inflammatory disorders. It is not known if IFN-λ4 has immunomodulatory activity. The expression of another type III IFN, IFN-λ3, is also controlled by genetic polymorphisms that are strongly linked to rs368234815. Therefore, it is of interest to compare these two IFNs for their effects on immune cells. Herein, using THP-1 cells, it was confirmed that IFN-λ4 could affect the differentiation status of macrophage-like cells and dendritic cells (DCs). The global gene expression changes induced by IFN-λ4 were also characterized in in vitro generated primary macrophages. Next, human PBMC-derived CD14 + monocytes were used to obtain M1 and M2 macrophages and DCs in the presence of IFN-λ3 or IFN-λ4. These DCs were cocultured with CD4 + Th cells derived from allogenic donors and their in vitro cytokine responses were measured. The specific activity of recombinant IFN-λ4 was much lower than that of IFN-λ3, as shown by induction of IFN-stimulated genes. M1 macrophages differentiated in the presence of IFN-λ4 showed higher IL-10 secretion than those differentiated in IFN-λ3. Coculture experiments suggested that IFN-λ4 could confer a Th2-biased phenotype to allogenic Th cells, wherein IFN-λ3, under similar circumstances, did not induce a significant bias toward either a Th1 or Th2 phenotype. This study shows for the first time that IFN-λ4 may influence immune responses by immunomodulation. Graphical Abstract: Human IFN-λ3 and IFN-λ4 modulate the differentiation of monocytes into macrophages and dendritic cells and influence their phenotypes.